2022
DOI: 10.3390/biomedicines10010195
|View full text |Cite
|
Sign up to set email alerts
|

Selective Isolation of Liver-Derived Extracellular Vesicles Redefines Performance of miRNA Biomarkers for Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. Definitive diagnosis of the progressive form, non-alcoholic steatohepatitis (NASH), requires liver biopsy, which is highly invasive and unsuited to early disease or tracking changes. Inadequate performance of current minimally invasive tools is a critical barrier to managing NAFLD burden. Altered circulating miRNA profiles show potential for minimally invasive tracking of NAFLD. The selective isolation of the circulating extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“… 461 The increased level of hepatocyte-derived EVs correlates with the severity of NASH; 462 therefore, the number of circulating EVs and their protein and miRNA composition might potentially be a powerful tool for NAFL/NASH diagnosis and treatment. 462 , 463 During lipid overload, miRNA-containing EVs derived from hepatocytes, including let-7e-5p and miR-210-3p, target adipocytes to promote lipid accumulation. 464 miRNAs in EVs released from lipotoxic hepatocytes (miR-128-3p is most effective) suppress PPARγ expression in HSC, leading to significantly upregulated expression of fibrotic genes, including Col1a1 and Atca1.…”
Section: Novel Signaling Pathways and Pharmacological Targetsmentioning
confidence: 99%
“… 461 The increased level of hepatocyte-derived EVs correlates with the severity of NASH; 462 therefore, the number of circulating EVs and their protein and miRNA composition might potentially be a powerful tool for NAFL/NASH diagnosis and treatment. 462 , 463 During lipid overload, miRNA-containing EVs derived from hepatocytes, including let-7e-5p and miR-210-3p, target adipocytes to promote lipid accumulation. 464 miRNAs in EVs released from lipotoxic hepatocytes (miR-128-3p is most effective) suppress PPARγ expression in HSC, leading to significantly upregulated expression of fibrotic genes, including Col1a1 and Atca1.…”
Section: Novel Signaling Pathways and Pharmacological Targetsmentioning
confidence: 99%
“…Increased expression of miR-128-3p was also identified in our recent work, alongside miR-122 and -192, in NAFL and NASH patient plasma EVs. This was only observed in circulating EVs derived specifically from hepatocytes (expressing ASGR1) [ 68 ]. Mitochondrial dysfunction and oxidative stress are common pathogenic events in fatty liver diseases related to both aetiologies, non-alcoholic and alcoholic (discussed in the following section) [ 69 ].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…These reports consistently support the notion that EVs preferentially enriched for tissue origin are most informative of disease and thus enhance sensitivity and specificity of biomarker analyses. We recently isolated hepatocyte-derived EVs by anti-ASGR1 immunoprecipitation for the study of DMET induction by rifampicin and in pregnancy [ 53 ] and to compare the performance of miRNA biomarkers for NAFLD in unfractionated plasma, global circulating EVs and liver-specific EVs [ 68 ]. Only in applying the selective isolation technique, was a strong significant trend observed in biomarker expression with disease severity in NAFLD patients; thereby providing the first evidence for the utility of tissue-specific EV isolation techniques to improve diagnostic performance in chronic liver disease.…”
Section: Immunobead- or Plate-based Capturementioning
confidence: 99%
“…Evidence supporting the endosomal origin of exosomes stems from observations that they contain proteins derived exclusively from the cytosol and are devoid of any nuclear proteins [ 188 ]. Initial proteomic analyses revealed that while exosomes harbor proteins specific to their cell and tissue of origin, for example integrins (e.g., α6β4, αvβ5, and α6β1 on breast cancer exosomes; αvβ3 and αvβ6 on prostate cancer exosomes; and β4 on pancreatic cancer exosomes), MHC class I and II on immune cell-derived exosomes, as shown for B lymphocytes and dendritic cells [ 189 , 190 , 191 ], prostate specific antigen (PSA) from prostate cells, asialoglycoprotein receptor 1 (ASGR1) from liver cells [ 192 ], microglial proteins (CD11b and CD45) from brain cells [ 193 ], placental alkaline phosphatase (PLAP) from placental cells [ 194 , 195 ], and Clara cell protein 16 (CC16) for exosomes produced and released by deep lung cells [ 196 ], they also contain proteins common to all exosomes irrespective of their cellular origin, which reflects a highly regulated sorting mechanism [ 186 , 197 ]. For instance, adapter protein ALG-2-interacting protein X (ALIX) and tumor susceptibility gene 101 (TSG101), two proteins extensively characterized for their roles in HIV budding (i.e., release of viral particles from the cell) and MVB formation [ 198 , 199 ], and several tetraspanins (CD63, CD81, CD9, and CD37) are present on all exosomes.…”
Section: Biogenesis and Function Of Exosomes In Normal And Pathologic...mentioning
confidence: 99%